Development and Evaluation of Setup Strategies in Printed Circuit Board Assembly - Yilmaz, Ihsan Onur.; SpringerLink (Online service) (Wiesbaden : Gabler, 2008)
The last decade has seen a rapid extension of electronic control devices for various types of technical products. In modern electronics manufacturing, highly automated assembly systems are used to mount the electronic components onto the printed circuit boards (PCBs). Maintaining high production flexibility in order to meet the desired product variety and, at the same time, achieving high utilization rates of the capital-intensive production equipment can only be achieved by applying highly sophisticated planning and control strategies for the operation of modern placement machines. Ihsan Onur Yilmaz develops a novel group setup strategy which integrates multiple problems of the PCB assembly, especially in a medium-variety production environment. At the core of his principle approach are the identification of similarities between different types of PCBs and the generation of PCB clusters upon which group setup strategies are based. The developed setup strategies are also innovative in the sense that they integrate the optimization of detailed machine operations. This integration has not been achieved in the classical approaches which primarily rely on statistical clustering techniques.
Technological Background -- SMT Placement Machines -- Production Planning in Electronics Assembly -- Development of Group Setup Strategies -- Numerical Investigation -- Conclusions.
Keywords: Business; Production management; Business and Management; Operations Management; Electronic books